FIRMS’ WAGE ADJUSTMENT DURING COVID-19: A LITERATURE SURVEY - Azim Azhar; Chen Chen Yong (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Firms’ wage adjustment provides a myriad of concerns for economic contemplation where issues stemming from product and labour market resulted from the demand and supply distortion that have created new and interesting puzzles which required further attention. The Covid-19 virus has recorded a remarkable wage adjustment among firms towards their workers in order to sustain the business during the catastrophic events. This study attempts to provide insight of articles related to firms’ wage adjustment during COVID-19. Papers related firms’ wage adjustment during COVID-19 from the year 2020 to 2023 that published in Web of Science were reviewed and critically discussed. This paper used PRISMA methodology for reporting the article extracted in systematic review. Findings showed that wage adjustment was significant response among firm during Covid-19 crisis, though government provide wage subsidies programmes, it just lasts for the short-run. This paper serves as an information bank for readers in obtaining a better understanding of firms’ wage adjustment behaviour during economic turbulence.